Endolymphatic Hydrops in Fluctuating Hearing Loss and Recurrent Vertigo - Domínguez, Pablo; Manrique-Huarte, Raquel; Suárez-Vega, Víctor; López-Laguna, Nieves; Guajardo, Carlos; Pérez-Fernández, Nicolás (Frontiers in Surgery, 2021)
Background: Endolymphatic hydrops (EH) is the histopathological hallmark of Ménière’s disease (MD) and has been found by in vivo MRI in patients with several inner ear syndromes without definite MD criteria. The incidence and relevance of this finding is under debate. Purpose: To evaluate the prevalence and characteristics of EH and audiovestibular test results in groups of patients with fluctuating audiovestibular symptoms not fulfilling the actual criteria for definite MD and compare them with a similar group of patients with definite MD and a group of patients with recent idiopathic sudden neurosensory hearing loss (ISSNHL). Material and methods: 170 patients were included, 83 with definite MD, 38 with fluctuating sensorineural hearing loss, 34 with recurrent vertigo and 15 with ISSNHL. The clinical variables, audiovestibular tests and EH were evaluated and compared. Logistic proportional hazards models were used to obtain the odds ratio for hydrops development, including a multivariable adjusted model for potential confounders. Results: no statistical differences between groups were found regarding disease duration, episodes, Tumarkin spells, migraine, vascular risk factors or vestibular tests; only hearing loss showed differences. Regarding EH we found significant differences between groups, with odds ratio (OR) for EH presence in definite MD group vs all other patients of 11.43 (4.5-29.02; p<0.001). If ISSNHL group was used as reference, OR was 55.2 (11.9-253.9; p<0.001) for the definite MD group, 9.9 (2.1-38.9; p=0.003) for the recurrent vertigo group and 5.1 (1.2-21.7; p=0.03) for the group with fluctuating sensorineural hearing loss. Conclusion: The percentage of patients with EH varies between groups. It is minimal in ISSNHL group and increases in groups with increasing fluctuating audiovestibular symptoms, with a rate of severe EH similar to the known rate of progression to definite MD in those groups, suggesting that presence of EH by MRI could be related to the risk of progression to definite MD. Thus, EH imaging in these patients is recommended.